Correlation of expression of lncRNA ZFAS1 and hsa-miR-372-3p in lung cancer tissues with the malignant characteristics and prognosis of patients - YANG Ye, DANG Rong-guang, ZHANG Jing, DONG Chao, SONG Xue-jing (Jichu yixue yu linchuang, 2022)
Objective To study the correlation of the expression of long non-coding RNA zinc finger antisense 1 (lncRNA ZFAS1) and hsa-miR-372-3p in lung cancer tissues with the malignant characteristics and prognosis of patients. Methods Eighty-two lung cancer patients hospitalized in Shijiazhuang People's Hospital from March 2015 to October 2016 were selected. The expression of ZFAS1 and miR-372-3p in lung cancer tissues and in adjacent tissues, the potential correlation of the level of ZFAS1 and miR-372-3p with malignant characteristics of patients were analyzed; Pearson method was used to analyze the relationship between ZFAS1 and miR-372-3p in lung cancer tissues; Kaplan-Meier was used to analyze the correlation of the expression of ZFAS1 and miR-372-3p with the prognosis of patients; COX regression was used to analyze the risk factors for poor prognosis of lung cancer patients. Results Compared with the situation of adjacent tissues, the expression of ZFAS1 and miR-372-3p in tumor tissue was significantly higher (P＜0.05). The expression of ZFAS1 and miR-372-3p in tumor tissue was related to TNM staging, lung membrane infiltration, whether lymph node metastasis occurred, and the degree of tumor differentiation (P＜0.05). The expression of ZFAS1 and miR-372-3p content in lung cancer tissues was significantly and positively correlated (r=0.477, P＜0.001). The 5-year survival rate of patients in the ZFAS1 and miR-372-3p high expression group was significantly lower than the low expression group (P＜0.05). TNM staging, lymph node metastasis, ZFAS1, and miR-372-3p were independent risk factors for poor prognosis in patients with lung cancer(P＜0.05). Conclusions ZFAS1 and miR-372-3p are highly expressed in lung cancer tissues and the expression level is related to the malignant characteristics and prognosis of lung cancer patients, so it may be regarded as an independent risk factor to predict poor prognosis of lung cancer patients.